The Dignified man in the contradictions of Jarir and Al-Farazdaq (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research studies the images of the dignified man in the contradictions of Jarir and Al-Farazdaq as linguistic, cognitive and aesthetic structures, in which both poets were able to shed light on the meanings of truth, goodness, and beauty. In contrast to what was known about contradictions, it was a text based on undermining the moral construction of the system of values ​​that formed the pillar of the message of Islam.  Which has been shortened to the hadith of the Prophet, may God bless him and grant him peace, saying: I was sent to prefect morals.The research sought to prove that the image of the dignified human being in contradictions did not depart from the religious and moral meanings of the concept of pride, which are the two types of faith, a description of the attributes of the divine self and the ideal human self. Strength had the greatest share, followed by the protection of the boundaries, the support of the truth, the abundance of helpers, and the enforcement of the word. The research also showed the bodies in which these images were decided, and the mechanism adopted by the two poets to bring them closer to the recipients, through the artistic and aesthetic values ​​contained in their poetry.